Formulasi Sediaan Denture Cleanser Dengan Ekstrak Siwak (Salvadora persica) Dan Uji Efektivitas Terhadap Bakteri Staphylococcus aureus - Dwi Astuti, Elsa; Fauzi, Ahmad; Fatihah Bintang Nugraha , Naywa (Journal of Pharmaceutical and Sciences, 2025)
Plaque buildup and bacterial accumulation on the surface of dentures are common problems faced by denture users. One alternative that can be used to clean dentures is miswak (Salvadora persica). Miswak contains many natural ingredients, including sodium chloride, potassium chloride, salvadourea, oleic acid, linoleic acid, trimethylamine, thiocyanate, benzyl isothiocyanate, and nitrate, silica, vitamin C, resin, tannin, saponin, N-benzyl-2 phenylacetamide, lignan, flavonoid, fluoride, calcium, sodium bicarbonate, and salvadorin. The purpose of this study was to formulate an effective denture cleanser from miswak extract using the Simplex Lattice Design (SLD) optimization method and to test its effectiveness against Staphylococcus aureus bacteria. The method used for the extraction process was the maceration method using 96% alcohol. For the antibacterial test of the denture cleanser preparation, the time kill assay method was used. The physical properties of the denture cleanser preparations were tested including organoleptic tests, clarity tests, pH tests, and viscosity tests. The results of the physical properties of the preparations in the organoleptic test for formulas 1 to 5 showed the characteristics of mint odor, brown color, and liquid form. The clarity test for all five formulas showed clear results and also no foreign particles and was declared to have met the requirements. The pH test results for the five formulas ranged from 6.28 ± 0.01 to 6.43 ± 0.01 and had met the requirements. The viscosity test did not meet the requirements because the results ranged from 10 ± 2 to 12.67 ± 1.15. The antibacterial test showed that there was no significant difference between all test groups regarding antibacterial activity.